The Effectiveness of Graphic Providers In Teaching Text Verbs of Accounts (Quasi Experimental Study In Public Junior High Schools) - Alfrida Randeabang, (Jurnal Pendidikan Indonesia, 2020)
This study was conducted under the considerations of the observation in SMPN 20 Kendari that many students found difficulties in understanding vocabulary. The objectives of this study were to find out the significance of the use of the graphic organizers on vocabulary achievement and to find out whether the use of graphic organizers for teaching vocabulary of recount text is effective to the eighth graders of SMPN 20 Kendari. To gain the objectives, the writer did a quasi experimental research by using non- randomized control group pretest-posttest design. The subjects of this study were the students in class 8A and 8H of SMPN 20 Kendari. 8A was the control group and 8H was the experimental group. In this study, the writer gave the students pre-test, treatment, and post-test. The pre-test was given to both groups using the same instrument. They were asked to answer some questions of vocabulary test. The treatment was given in three meetings. The treatment in the experimental group was using graphic organizers, while the treatment in the control group was lecturing. The post-test was conducted after the treatment given to both groups using the same instrument as the pre-test but the position of question numbers were reshuffled. The result of the analysis using t-test showed that the experimental group got better score than the control group. In the pre-test, the average score of the experimental group was 68.87 and the control group was 68.39. In the post-test, the average score of experimental group was 83.55 and the control group was 74.52. tTe result of the t-test was 2.14 and t-table was 2.00. It means that the t- value was higher than t-table (2.14>2.00). In conclusion, graphic organizers were effective to improve students‟ mastery of vocabulary in recount text. Moreover, the writer hopes that the other English teachers would use graphic organizers as one of strategies in teaching vocabulary.